Analisis Pengaruh Kualitas Layanan Pijat Online Terhadap Tingkat Kepuasan Konsumen - Athanya Adinda; Gladiola Asti Arsoputri; Teuku Ghiyas Kausara; Wilhan Chua (Indonesian Business Review, 2019)
As time passes by, critical assessment of consumer has become the key factor that determines the success of a service. Partnering with massage therapists as their talents has become a challenge for massage service company to ensure the consistency of its quality. This study focuses on how consumers assess the quality of massage service provided by one of the online massage service company (Tangible, Reliability, Responsiveness, Empathy, Assurance) that will affect the level of consumer satisfaction and repeat purchase. A quantitative approach is used through the dissemination of the survey. Results show that all of the variables, except the Tangible and responsiveness, will affect the level of consumer satisfaction. Furthermore, it is also proven that satisfied consumers will decide to make repeat purchase.